Identification and Prevalention of Parasite in Big eye scad (Selar crumenophthalmus) on Fish Auction in Sibolga - M, Dian Fitria; Ghazali, Tengku Muhammad; Firmansyah, Rodhi; Sibuea, Noni Ummu Salama; Bagariang, Ramona Indah; Matondang, Syahril Ramadhan (Jurnal Perikanan dan Kelautan, 2020)
Big eye scad fish with the Latin name Selar crumenophthalmus is one type of small pelagic fish that has economic value. Life of benthic fish populations in the salt water, is inseparable from parasitic infestations. Fish parasites are one of the important problems in fisheries biology. Researchers examined parasites on bentong selar fish originating from fish auction sites in the Sibolga area. The research data obtained are several species of parasites and the prevalence rate of each parasite that attacks big eye scad fish, such as: Acanthocephala spp. 14.28%, Anisakis simplex 2.86%, Norileca indica 2.86% and Digenea 5.71%.